Programa radial y la prevención de la violencia de género contra las mujeres en la Parroquia Velasco Ibarra, del Cantón El Empalme - Aspiazu Carriel, Cindy Geovanna (2019)
Violence against women constitutes a public health problem and a violation of human rights. That is why it is persevered that the radio stations of the Empalme canton produce programs with themes that contribute to the community, one of the main cases is to eradicate gender violence; aggressions against women occur daily, cases of femicide have grown according to statistics in this period, social communicators can contribute positively since the content they broadcast influences the listeners tuning to the radio stations. This type of violence against the female sex crosses borders and can be manifested in any social environment, intimidation can not only be physically but also of a psychological, manipulative nature where the victim is an easy victim of the victimizer and has to continue suffering this type of difficulties, but what leads to a woman having to endure this atmosphere of violence? Unfortunately, our culture and, above all, the Latin culture, machismo is fostered where we have evolved in a technological but not intellectual way, it is not uncommon to hear mothers or fathers say “For a reason it is a man” what affects the human being to act with violence versus another when it does not meet your desired expectations. The production of the prevention program against women will seek support from public and private organizations that support this cause, a report will also be presented to the brands seeking sponsors, the objective of the radio program is to help those who are victims and who do not They know what to do